Evaluation of carbon supported platinum–ruthenium nanoparticles for ammonia electro-oxidation: Combined fuel cell and electrochemical approach. (5th January 2017) - Silva, Júlio César M.; Ntais, Spyridon; Teixeira-Neto, Érico; Spinacé, Estevam V.; Cui, Xiaoyu; Neto, Almir O.; Baranova, Elena A.
Abstract: Ammonia electro-oxidation reaction (AmER) was investigated by using conventional electrochemical experiments, direct ammonia fuel cell (DAFC) and galvanostatic electrolysis experiments. The working electrode/anodes were composed of carbon supported PtRu/C nanoparticles (NPs) with atomic Pt:Ru ratios of 100:0, 90:10, 70:30 and 50:50. The resulting nanoparticles ranged between 5.1 and 7.3 nm in size depending on the Ru content and were analyzed by XRD, TEM and synchrotron radiation photoelectron Spectroscopy (SRPES). Alloying Pt with Ru shifted AmER to the lower onset potentials compared to Pt/C. Among nanostructured PtRu/C electrocatalysts, the Pt90 Ru10 composition showed the best activity and stability in the conventional electrochemical (cyclic voltammetry and chronoamperometry) experiments, DAFC and 8 h galvanostatic electrolysis. The concentration of nitrite and nitrate was doubled using PtRu/C 90:10 compared to Pt/C, because of excess of OHads species formed on Ru. The results show that the addition of small amount of Ru to Pt NPs improves the AmER due to additional formation of OHads that promote the reaction on alloyed PtRu nanoparticles. Highlights: Ammonia oxidation reaction investigated on carbon-supported PtRu alloys. Various Pt:Ru atomic ratios were studied: 100:0, 90:10, 70:30 and 50:50. Pt90 Ru10 /C catalyst is the most active in electrochemical and fuel cell experiments. Main products of ammonia oxidation are nitrogen, nitrate and nitrite. 10 at% of Ru improves the reaction by supplying OHads .